Perbandingan antara metode hydrodistilation dan hydro steam distilation terhadap jumlah rendemen dan karakteristik aroma minyak terbang kulit jeruk lemon (Citrus limon L) - Abil Fadila; Sarifah Nurjanah; S.Rosalinda Rosalinda (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Lemon contains essential oil compounds found in the peel, namely the flavedo. This section can produce essential oils by various methods, including the distillation method. Differences in distillation methods can affect the quality of essential oils. In the essential oil production process, paying attention to the distillation method and the samples of raw materials used is necessary. This study compares the process of extracting lemon peel oil using hydrodistillation and hydro-steam distillation methods.This research has enormous benefits for obtaining the best essential oils using a method that has stable quality and at a not too high cost. The process conditions are carried out by applying the influence factors of temperature, distillation time, and the ratio of raw materials to yield and aroma characteristics. The heating temperature is 100 oC, the distillation time is 4 hours, the raw material ratio is 1:5, as well as the pretreatment process of raw materials. The resulting steam is condensed, and the distillate, a mixture of oil and water, is separated using a separatory funnel. The oil is purified with anhydrous sodium sulfate (Na2SO4) to separate the oil from the remaining water. The best results were obtained from the research results in the hydrodistillation method with a heating temperature of 100 oC, a distillation time of 4 hours, and a raw material size of 1 cm with a % yield of 0.99%. As well as, the aroma produced is not too strong to get a value of 1 for the hydrodistillation method, and the aroma characteristics are quite strong with a scale of 3 produced by the hydro-steam distillation method. As well as the % yield value generated is 0.495%.